Training On Growth Monitoring Of Children In The Work Area Of Kayuwou Health Center: Pelatihan Pemantauan Pertumbuhan Balita Di Wilayah Kerja Puskesmas Kayuwou - Dwi Erma Kusumawati; Nurjaya; Dias Astiza (Poltekkes Kemenkes Palu, 2021)
Growth monitoring is part of the health service activities carried out for infants and toddlers. It aims to improve the quality of early childhood growth and development and the readiness of children to enter formal education which is directed at improving the nutritional, cognitive, mental and psychological health status of children. The population and sample in this study were 13 Posyandu located in the working area of the Kayuwou Public Health Center, Sindue Tobata District, Donggala Regency. The results show that the correct Posyandu in measuring body weight is only 15.3%, incorrect as much as 84.7%, the measurement of body length and height is only FOUR Posyandu that take measurements of body length and height and in their use fall into the category not exactly. For the correct Posyandu in filling out the KMS and Determining Growth Status, there is only ONE Posyandu (7.7%). The conclusion of this community service shows an increase in cadres in anthropometric measurements, filling KMS and determining growth status. This community service is important to provide knowledge and improve the skills needed by cadres to be able to determine the nutritional status of toddlers properly and correctly